TIGIT-CD155 interactions in melanoma: a novel co-inhibitory pathway with potential for clinical intervention - Mahnke, Karsten; Enk, Alexander (The journal of investigative dermatology, 2016)
Inozume et al. describe a novel immunosuppressive mechanism in melanoma that is triggered by the interaction between CD155 (expressed by melanomas) and T-cell Ig and ITIM domain (TIGIT) (expressed by tumor infiltrating lymphocytes). This pathway exists in addition to the "classical" co-inhibitory PD-1-PD-L1 pathway. Hence, the combinatorial blockage of both pathways by specific antibodies resulted in the greatly enhanced effector function of melanoma-specific cytotoxic T cells. Given that CD155-TIGIT signaling exerts potent inhibitory action in different subsets of immune cells and that CD155 is expressed broadly in several tumor entities, this report points toward a novel and promising therapeutic strategy to combine different checkpoint blocking agents for greater success in antitumor therapy.